The Application Of Integrated Accounting Information System Using Microsoft Access At Bakso Cak Tello - Riksen Sitorus; Hendi Hendi (ConCEPt - Conference on Community Engagement Project, 2023)
Micro, small, and medium enterprises are classified as economic entities that are vulnerable to the effects of uncertainty. The main thing that underlies the previous statement is the lack of role of accounting in managing the business. Bakso Cak Tello as a partner for community service is a business that has not yet implemented accounting aspects. Partners keep no records at all making it difficult to reliably observe the economic status of the business. This project has the goal of providing an integrated accounting recording system using Microsoft Access software. This system is designed using primary and secondary data obtained through interviews, observations, literature studies, and documentation from partners. The system is designed in such a way as to be able to facilitate the needs of partners starting from recording transactions, and computing, to financial reports according to an effective and efficient manner referring to related standards, namely the SAK EMKM. The result of this project shows that the designed system is able to accommodate partners to see every transaction that has been recorded and can be a basis for consideration for partners to develop business. Partners can take advantage of available financial reports to analyse business conditions. The next project can use other software that is considered suitable, effective, and efficient for partners or by adding other features. Micro, small, and medium enterprises are classified as economic entities that are vulnerable to the effects of uncertainty. The main thing that underlies the previous statement is the lack of role of accounting in managing the business. Bakso Cak Tello as a partner for community service is a business that has not yet implemented accounting aspects. Partners keep no records at all making it difficult to reliably observe the economic status of the business. This project has the goal of providing an integrated accounting recording system using Microsoft Access software. This system is designed using primary and secondary data obtained through interviews, observations, literature studies, and documentation from partners. The system is designed in such a way as to be able to facilitate the needs of partners starting from recording transactions, and computing, to financial reports according to an effective and efficient manner referring to related standards, namely the SAK EMKM. The result of this project shows that the designed system is able to accommodate partners to see every transaction that has been recorded and can be a basis for consideration for partners to develop business. Partners can take advantage of available financial reports to analyse business conditions. The next project can use other software that is considered suitable, effective, and efficient for partners or by adding other features.